Dermoid Cyst of the Orbit : An Unusual Presentation. - Verma, Richa; Sharma, Navneet (Journal of Medical Biomedical and Applied Sciences, 2020)
Dermoid cysts of the orbit are uncommon orbital tumours that occur primarily in the pediatric population. They are divided into deep and superficial lesions with deep lesions presenting later in life. Depending on the location, size, the patient may present proptosis, diplopia, and restriction of eye movements. We describe a case of a dermoid cyst involving the lateral aspect of orbit of an adult presented with unusual complaints. A 17 years old female presented with complaints of presence of hair along superior palpebral fissure and itching right eye for one month. This clinical picture pointed towards the diagnosis of dermoid cyst. USG and CT scan were preformed and diagnosis of dermoid cyst was confirmed.